Project Management / Sixth Edition - Lock Dennis (Gower Publishing, 1996)
Nature and Organization of Project Management, The Financial and Commercial Framework, Planning and Scheduling, Computer Applications, Purchasing and Materials Management, Managing Work and Costs, Index.